2017
DOI: 10.20853/32-1-1657
|View full text |Cite
|
Sign up to set email alerts
|

Effects of demographic factors on provision of feedback in postgraduate medical education

Abstract: A key element in the process of clinical medical education is the process of providing feedback by comparing the directly observed performance of postgraduate doctors training to become specialists to that of a previously identified and communicated 'gold standard' and incorporating a plan for improvement. This is regarded as crucial to enhance clinical competencies. Hence, a greater understanding of the clinical educational environment and the various factors that impact on the giving and receiving of feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
(63 reference statements)
2
4
0
Order By: Relevance
“…Previous studies found that 'older, more experienced consultants were more confident about providing feedback' , and seniority of the consultant affected how feedback was received as senior consultants were held in higher esteem. 10 However, similar to our findings, previous studies found that 'male consultants felt more comfortable giving constructive feedback as compared to females' , 21 and 'males felt that feedback sessions were always successful' . 10 Our study found that male trainers felt more confident about their feedback skills and gave feedback more frequently than female counterparts.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Previous studies found that 'older, more experienced consultants were more confident about providing feedback' , and seniority of the consultant affected how feedback was received as senior consultants were held in higher esteem. 10 However, similar to our findings, previous studies found that 'male consultants felt more comfortable giving constructive feedback as compared to females' , 21 and 'males felt that feedback sessions were always successful' . 10 Our study found that male trainers felt more confident about their feedback skills and gave feedback more frequently than female counterparts.…”
Section: Discussionsupporting
confidence: 90%
“…10 However, similar to our findings, previous studies found that 'male consultants felt more comfortable giving constructive feedback as compared to females' , 21 and 'males felt that feedback sessions were always successful' . 10 Our study found that male trainers felt more confident about their feedback skills and gave feedback more frequently than female counterparts. This highlights a need to create more enabling environments and to address possible power influences based on gender.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations